2010
DOI: 10.2478/s11686-010-0006-6
|View full text |Cite
|
Sign up to set email alerts
|

An accidental attachment of Elthusa raynaudii (Isopoda, Cymothoidae) in Etmopterus sp. (Squaliformes, Etmopteridae)

Abstract: A female Elthusa raynaudii was found attached on the roof of the mouth facing inward in a lantern shark, Etmopterus sp. in Taiwan. This was backwards to all known cymothoid attachments in the mouths of fishes. This isopod naturally occurs in the gill chamber of fishes. The attachment must have occurred accidentally. This is only the fourth time this isopod has been collected in the northern hemisphere and the first for Taiwan and this host.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(5 reference statements)
1
2
0
1
Order By: Relevance
“…The isopod in this odd location probably was either introduced to the mouth of L. sceleratus while preying on its natural host or the parasite migrated from the gill cavity to the mouth after death of the captured L. sceleratus . The same odd cases for this isopod species were reported by Hurley ( 1961 ) (in New Zealand) and Williams et al ( 2010 ) (in Taiwan) from the stomach and the roof of the mouth of shark, respectively, and they described the cases as being accidental. The isopod L. raynaudii was originally described from the Cape of Good Hope in South Africa (Milne-Edwards 1840 ) from unknown host and also recorded several times from a wide range of localities within the Indo-Pacific region and sub-Saharan Africa (Van der Wal et al 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…The isopod in this odd location probably was either introduced to the mouth of L. sceleratus while preying on its natural host or the parasite migrated from the gill cavity to the mouth after death of the captured L. sceleratus . The same odd cases for this isopod species were reported by Hurley ( 1961 ) (in New Zealand) and Williams et al ( 2010 ) (in Taiwan) from the stomach and the roof of the mouth of shark, respectively, and they described the cases as being accidental. The isopod L. raynaudii was originally described from the Cape of Good Hope in South Africa (Milne-Edwards 1840 ) from unknown host and also recorded several times from a wide range of localities within the Indo-Pacific region and sub-Saharan Africa (Van der Wal et al 2019 ).…”
Section: Discussionsupporting
confidence: 81%
“…Williams et al (2010) reported, as an accidental case in Taiwan, Elthusa raynaudii from the palate of a lantern shark specimen that was later designated as the holotype of Etmopterus joungi Knuckey, Ebert, and Burgess, 2011. However, the attachment site, host taxon (i.e., elasmobranch fish), and the large pleotelson shown in a photograph of Williams et al (2010) suggest that their specimen might also be E. splendida rather than E. raynaudii. This specimen (California Academy of Science; CASIZ 180277) needs to be further examined in future research.…”
Section: Resultsmentioning
confidence: 99%
“…La mayoría de este grupo de peces pertenecen a familias de hábitos demersales, como Sciaenidae y Serranidae. De manera general, estos isópodos aparentan tener preferencia por los peces óseos (Trilles & Öktener, 2004;Williams et al 2010).…”
unclassified